Invasive Galega officinalis (Goat's rue) plants in Canada form a symbiotic association with strains of Neorhizobium galegae sv. officinalis originating from the Old World - Bromfield, Eden S. P. (Ecol Evol, 2019)
The toxic legume plant, Galega officinalis, is native to the Eastern Mediterranean and Black Sea regions. This legume is considered to be a noxious weed, and its establishment in Canada may have resulted from ornamental planting and/or field trials. In its native range, a highly specific nitrogen‐fixing symbiosis with the bacterium, Neorhizobium galegae symbiovar (sv.) officinalis, is required for normal growth. In North America, nothing is known about the bacterial symbionts of G. officinalis. Our purpose was to determine the species and symbiovar identity of symbiotic bacteria associated with invasive plants of G. officinalis at five sites in the province of Ontario, Canada.  Sequence analysis of four housekeeping (16S rRNA, atpD, glnII, and recA) and two symbiosis (nodC and nifH) genes showed that all 50 bacterial isolates from root nodules of G. officinalis at the five Canadian sites were identical to strains of N. galegae sv. officinalis originating either from Europe or the Caucasus. Plant tests indicated that soils collected from four Canadian sites without a history of agriculture or presence of G. officinalis were deficient in symbiotic bacteria capable of eliciting nodules on this plant. Collectively our data support the hypothesis of anthropogenic co‐introduction of G. officinalis and its specific symbiotic bacterium into Canada from the Old World. Factors that may limit the spread of G. officinalis in new environments are discussed.